THE EFFECT OF CINNAMON EXTRACT ON ANTIOXIDANT ACTIVITY, TOTAL BAL, PH, AND HEDONICS OF RED BEET YOGHURT - Legowo, Anang Mohamad; Wardhani, Febrianinta; Siti Susanti (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2024)
Red beet yogurt needs improvement, especially in terms of flavor. The addition of cinnamon can improve hedonic quality, especially aroma, taste, and overall acceptance. This study aims to determine the effect of cinnamon extract on antioxidant activity, total LAB, pH, and hedonic. The research method used RAL with the addition of cinnamon extract 0%, 0.1%, 0.3%, 0.5% and 0.7%. Antioxidants were tested using the DPPH method, total LAB was calculated using the TPC method, pH was measured using a pH meter, and hedonic using the scoring method. The results showed that the addition of cinnamon extract had a significant effect (p<0.05) on total LAB, pH, and hedonic with attributes of aroma, color, taste, texture, and overall preference. The most optimal treatment was a cinnamon extract concentration of 0.3% because it produced an optimum level of preference with antioxidant activity of 22.41%, total LAB of 9.36 Log CFU/ml, and pH of 4.02.